2018
DOI: 10.1063/1.5027086
|View full text |Cite
|
Sign up to set email alerts
|

Drift turbulence, particle transport, and anomalous dissipation at the reconnecting magnetopause

Abstract: Using fully kinetic 3D simulations, the reconnection dynamics of asymmetric current sheets are examined at the Earth's magnetopause. The plasma parameters are selected to model MMS magnetopause diffusion region crossings with guide fields of 0.1, 0.4, and 1 of the reconnecting magnetosheath field. In each case, strong drift-wave fluctuations are observed in the lower-hybrid frequency range at the steep density gradient across the magnetospheric separatrix. These fluctuations give rise to cross-field electron p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
61
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(69 citation statements)
references
References 92 publications
8
61
0
Order By: Relevance
“…The MMS observations also reveal that electrons are often frozen‐in to the fluctuations (Graham et al, ). Previous simulations based on this event and two others (Le et al, ) revealed the development of drift wave fluctuations as well as noting the accompanying enhancement of cross‐field electron transport and parallel heating. These results complemented discussions of transport by lower‐hybrid turbulence across magnetopause boundary layers in the context of hybrid simulations (Gary & Sgro, ) as well as Cluster (Vaivads et al, ) and MMS observations (Graham et al, ).…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…The MMS observations also reveal that electrons are often frozen‐in to the fluctuations (Graham et al, ). Previous simulations based on this event and two others (Le et al, ) revealed the development of drift wave fluctuations as well as noting the accompanying enhancement of cross‐field electron transport and parallel heating. These results complemented discussions of transport by lower‐hybrid turbulence across magnetopause boundary layers in the context of hybrid simulations (Gary & Sgro, ) as well as Cluster (Vaivads et al, ) and MMS observations (Graham et al, ).…”
Section: Introductionsupporting
confidence: 57%
“…However, whether the strong turbulence measured at the magnetopause actually drives transport or produces the necessary dissipation remain open questions as previous three‐dimensional simulations of reconnection‐driven turbulence did not adequately address the impact of frozen‐in electrons on transport (Le et al, , ; Price et al, , ). The turbulence that develops in the strong density gradient across the magnetopause has characteristic time scales that are intermediate between the electron and ion gyrofrequencies.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the main contribution to the electron dissipation parameter comes from the off-diagonal components of the pressure tensor and traceless strain rate tensor D (e) 5 = −2Π (e) xz D (e) xz (blue frames in Figure 2) suggesting the energy transfer between the perpendicular and parallel to the magnetic field components of the electron velocity distribution. At the same time, the spatial distribution of the electron dissipation Pi-D (e) shown in Figure 1d suggests that it is provided by the LHDI, which is indeed known to heat electrons (Daughton et al, 2004;Huba et al, 1977;Le et al, 2018). Strong LHDI activity was found in 3-D PIC simulations of reconnection (Roytershteyn et al, 2012) and DFs (Divin et al, 2015;Lapenta et al, 2014;Sitnov et al, 2014) as well as in their space yz .…”
Section: Simulation Setup and Resultsmentioning
confidence: 78%
“…Observations of magnetic reconnection at the Earth's magnetopause regularly indicate nearby strong wave activity and/or turbulence (e.g., Eastwood et al, 2009), particularly at the magnetopause current sheet adjacent to the electron diffusion region (EDR) on the magnetosphere side Chen et al, 2017;Ergun et al, 2017). This turbulence or activity appears as strong fluctuations in the magnetic field (B) and particle density (n) and may be a result from the unstable current sheet adjacent to the magnetic reconnection region (e.g., Daughton, 2003;Daughton et al, 2004;Daughton et al, 2011;Ergun et al, 2017;Ji et al, 2004Ji et al, , 2005Karimabadi et al, 2007;Lapenta et al, 2006;Le et al, 2018;Nakamura et al, 2016;Price et al, 2016Price et al, , 2017Roytershteyn et al, 2012Roytershteyn et al, , 2013. These instabilities are of importance as they may influence the magnetic reconnection evolution and influence the three-dimensional (3-D) structure of magnetic reconnection.…”
Section: Introductionmentioning
confidence: 99%